The Guadaira Greenbelt (Seville): analysis and evaluation of a peri-urban rehabilitation proposal - David Cristell Gómez Montblanch; Manuel Jesús Marchena Gómez; Rafael Cámara Artigas (Investigaciones Geográficas)
The river Guadaira in its lower course has undergone various transformations, from historical interventions for the installation of water mills, to those made in the riverbed since the beginning of the 20th century to mitigate floods in the city of Seville. A critical analysis and assessment is made of proposed ‘Guadaira Greenbelt’ for the recovery of the marginal peri-urban space linked to the most recent transformation of the river in 1977. The ecological and social scope of this proposal is analysed and evaluated in a SWOT analysis, with a clearly socio-environmental objective that seeks the sustainability of the area, which is discussed in comparison other national and international experiences. The conclusions highlight the errors related to the Mediterranean riparian plant formations, which is one of the most important weaknesses of the proposal. The research concludes that the proposal meets the objectives of the ENRR, but does not adapt to the academic patterns on research on river and river restoration.